(untitled) (Revista Brasileira de Computação Aplicada, 2016)
Nowadays, there are hundreds of underway worldwide projects to redesign both com- munication protocols and architecture of the Internet. These initiatives are collectively called “future Internet” research. Most of these initiatives rely on existing distributed systems, which often limit or even prevent the development of “clean slate” solutions. The main reason is that the great majority of distributed systems are tightly-linked with the TCP/IP protocol stack. In this article, we provide a first glance discussion on the relationships between future Internet and distributed systems research, focusing on dependencies and similar requirements among these areas. From this analysis, it beco- mes evident that many of the future Internet requirements (and open challenges) are repeated in the distributed systems landscape. Although there are many studies on both research fronts individually, the study of the key challenges of future Internet when addressing distributed systems requirements is a topic yet not explored in our contemporary research. This paper aims at determining the gaps and requirements future Internet must fulfill in order to support future distributed systems. To support this objective, a set of design metrics are identified and a convergent design space is proposed.